서비스디자인 기반의 고려인 이주민을 위한 간호대학생 봉사활동 개발 - 김희영(Heeyoung Kim) (한국콘텐츠학회 논문지, 20(6), 2020)
The number of Goryeo-in immigrants has been increasing recently. National attention and active interactions are required for them to settle down with the identity of Koreans. The purpose of this study was to develop volunteer activity for Goryeo-in immigrants based on service design. The study was performed in G metropolitan city from October to November 2019. The participants were 33 Goryeo-in immigrants and 3 stakeholders. Data was collected through a survey and interviews of Goryeo-in immigrants and stakeholder interviews. In the field surveys and interviews, it was found out that the main problems faced by Goryeo-in immigrants were communication difficulties, maladjustment, job insecurity and smoking. The core issue was defined as 'How Goryeo-in immigrant women can improve their communicate ability in Korean'. In order to solve this problem we developed a program called 'Goryeo-in Han-gul ssugssug' for volunteer activities, and the program delivered through a storyboard and a role play. Using the service design process, a meaningful volunteer activity was designed considering lots of situation of Goryeo-in immigrants and nursing students in various ways. This study shows that the service design methodology is a useful way to reflect the needs of consumers and volunteers in developing volunteer work. 최근 증가하는 고려인 이주민이 한국인이라는 정체성을 가지고 정착하기 위해서는 국민적 관심과 적극적인 교류가 필요하다. 본 연구는 고려인 이주민을 위한 간호대학생의 봉사활동을 서비스디자인 기반으로 개발하기 위함이다. 2019년 10월부터 11월까지 G 광역시에서 수행되었으며 참여자는 고려인 이주민 33명과 이해관계자 3명이었다. 자료수집은 고려인 이주민 대상으로 설문조사와 면담, 이해관계자 면담을 실시하였다. 조사결과 고려인 이주민이 직면하는 주요문제로 발견된 것은 의사소통의 어려움, 부적응, 고용 불안정, 흡연이었다. 핵심이슈를 '어떻게 하면 고려인 이주여성이 한국어 소통능력을 향상시킬 수 있을까'로 정의하였고 문제해결을 위해 간호대학생의 봉사활동 '고려인 한글 쑥쑥' 프로그램을 개발하였으며, 스토리보드와 역할극을 통해 전달하였다. 서비스디자인 프로세스를 활용하여 고려인 이주민과 간호대학생의 상황을 다각도로 고려한 의미 있는 봉사활동을 설계할 수 있었다. 본 연구를 통해 서비스디자인 방법론은 봉사활동을 개발함에 있어 수요자와 봉사자의 요구를 반영할 수 있는 유용한 전략임을 알 수 있다.